A OPTIMALISASI PRODUKTIVITAS DAN PENJUALAN MENGUNAKAN METODE INTEGER PROGRAMMING - Emmy Junianti; John EHJ FoEh (Jurnal Kajian Ilmiah, 2022)
This article reviews previous studies as theoretical reinforcement or the basis for further research. This article examines the optimization of productivity and sales of Pempek Palembang using the integer programming method. This study aims to determine the combination of production at Warung Pempek Serasan in order to create an effective and efficient pattern to create maximum profit. The results of this study are: 1) Production optimization using the integer programming method can be used to find the maximum production mix in order to get the best production results 2) Using the economic order quantity (EOQ) can be calculated maximum or minimum stock/inventory so that the stock of raw materials is not experiencing shortages or buildup; 3) Calculating the break even point (BEP) can be used as a reference for profit targets that must be obtained in the sale of a product.